Analisis Efektivitas Transportasi Ojek Online Sebagai Pilihan Moda Transportasi di Kota Samarinda - Siva Aulia Maulida; Findia Findia; Zony Yulfadli (SENTRI: Jurnal Riset Ilmiah, 2026)
This study aims to explicitly analyze the effectiveness of online motorcycle taxis as a preferred mode of transportation in Samarinda City by evaluating four key service dimensions, namely cost, punctuality, service quality, and safety. This research is important because although online motorcycle taxis offer flexibility, accessibility, and time efficiency, their level of effectiveness may differ across regions and is strongly influenced by local urban characteristics and user mobility needs. This study employs a descriptive quantitative approach with a total of 100 respondents consisting of Grab, Gojek, and Maxim users in Samarinda, selected during the period of October to November 2025. Data were collected using a structured questionnaire and analyzed through descriptive statistical techniques and frequency distribution to obtain mean scores and categorical interpretations for each service dimension. The results show that all variables fall into the good category, where the cost variable recorded the highest mean score of 4.03, indicating that price transparency and affordability play a dominant role in shaping user satisfaction. Punctuality, service quality, and safety also received positive assessments, demonstrating that online motorcycle taxi services are able to meet users’ mobility needs efficiently and reliably. These findings strengthen empirical evidence regarding the effectiveness of online transportation services in secondary urban regions such as Samarinda and provide practical implications for service providers and policymakers to prioritize continuous improvement in cost efficiency, service reliability, and safety performance to enhance user trust and service sustainability.